Constructing Hypoxia‐Tolerant and Host Tumor‐Enriched Aggregation‐Induced Emission Photosensitizer for Suppressing Malignant Tumors Relapse and Metastasis. Issue 40 (7th September 2022) - Cui, Shisheng; Dai, Shuangxiong; Lin, Na; Wu, Xinghui; Shi, Jianbing; Tong, Bin; Liu, Pai; Cai, Zhengxu; Dong, Yuping
Abstract: Photodynamic immunotherapy is a promising treatment strategy that destroys primary tumors and inhibits the metastasis and relapse of distant tumors. As reactive oxygen species are an intermediary for triggering immune responses, photosensitizers (PSs) that can actively target and efficiently trigger oxidative stress are urgently required. Herein, pyrrolo[3, 2‐b]pyrrole as an electronic donor is introduced in acceptor–donor–acceptor skeleton PSs (TP‐IS1 and TP‐IS2) with aggregation‐induced emission properties and high absorptivity. Meanwhile, pyrrolo[3, 2‐b]pyrrole derivatives innovatively prove their ability of type I photoreaction, indicating their promising hypoxia‐tolerant advantages. Moreover, M1 macrophages depicting an ultrafast delivery through the cell‐to‐cell tunneling nanotube pathway emerge to construct TP‐IS1@M1 by coating the photosensitizer TP‐IS1. Under low concentration of TP‐IS1@M1, an effective immune response of TP‐IS1@M1 is demonstrated by releasing damage‐associated molecular patterns, maturating dendritic cells, and vanishing the distant tumor. These findings reveal insights into developing hypoxia‐tolerant PSs and an efficient delivery method with unprecedented performance against tumor metastasis. Abstract : Herein, two hypoxia‐tolerant aggregation‐induced emission photosensitizers (TP‐IS1 and TP‐IS2) are constructed with an acceptor–donor–acceptor skeleton. Moreover, M1 macrophages depicting an ultrafast delivery and efficient enrichment through the cell‐to‐cell tunneling nanotube pathway emerge to construct TP‐IS1@M1. Under low concentration of TP‐IS1@M1, an effective immune response of TP‐IS1@M1 is demonstrated by releasing damage‐associated molecular patterns, maturating dendritic cells, and vanishing the distant tumor.